PEDAGOGICAL SYSTEM OF FORMATION OF PROFESSIONAL COMPETENCIES OF STUDENTS - THE FUTURE OF SPECIALISTS IN CUSTOMS - Natalya V. Baikina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article describes the pedagogical system of the professional competencies of the students - the future of specialists in customs. The definition of technology of formation of professional competence. Curriculum divides the educational process in the three cycles: humanitarian, social and economic cycle; mathematical and natural cycle and a professional cycle. The principles of modulus of each learning cycle. The content of each cycle, the discipline help form professional competencies. Submitted by the modulus structure of basic educational training program of customs. The series of approvals technology of formation of professional competencies in the educational process of training specialists in the de-partment USATSK SamGTU.